Support in Schools and School Well-Being: Self Esteem as a Mediator - Muhammmad Ahkam Alwi; Dewi Retno Suminar; Nur Ainy Fardana Nawangsari (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2020)
Well-being at school is the hope for all students, helping them to survive their time there. However, many pupils experience low levels of well-being, which has an impact on their psychological state and academic outcomes. The purpose of this study is to determine whether social support in schools can strengthen the well-being of high school students in Surabaya. The approach taken in the research is quantitative correlational study. Data collection was made using self-report questionnaires to measure school well-being, support in schools, and self-esteem. The participants were 220 high school students. Path analysis procedures were performed to address the hypothesis; the results show that teachers’ social support and friend social are related to direct and indirect school well-being mediated by self-esteem. The study suggests that students can improve their well-being through support from school and their own self-esteem, and that policymakers in schools, mainly school principals and teachers, can also improve such well-being. The limitations and implications of the findings are discussed for future research.